2018
DOI: 10.20944/preprints201809.0560.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inverse Multiquadratic Functions as Basis for Rectangular Collocation Method to Solve the Vibrational Schrödinger Equation

Abstract: We explore the use of inverse multiquadratic (IMQ) functions as basis functions when solving the vibrational Schrödinger equation with the rectangular collocation method. The quality of the vibrational spectrum of formaldehyde (in six dimensions) is compared to that obtained using Gaussian basis functions when using different numbers of width-optimized IMQ functions. The effects of the ratio of the number of collocation points to the number of basis functions and of the choice of the IMQ exponent are studied. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…We have recently shown that collocation works well even when the basis functions do not satisfy the integrability condition. 60 (iii) Because energy levels can be computed with basis functions that have no amplitude at singularities (even when wavefunctions have significant amplitude at the singularities) and it is not necessary to approximate integrals, singularities cause no problems. 31 (iv) The basis is deemed complete if, at the M>N collocation points,…”
Section: Collocation and Its Advantagesmentioning
confidence: 99%
“…We have recently shown that collocation works well even when the basis functions do not satisfy the integrability condition. 60 (iii) Because energy levels can be computed with basis functions that have no amplitude at singularities (even when wavefunctions have significant amplitude at the singularities) and it is not necessary to approximate integrals, singularities cause no problems. 31 (iv) The basis is deemed complete if, at the M>N collocation points,…”
Section: Collocation and Its Advantagesmentioning
confidence: 99%
“…With expansion functions that satisfy the differential equation but not the boundary conditions, one gets series methods [33] or the Method of Fundamental Solutions (MFS) [3,13] or lightning or log-lightning methods for PDE problems with corner singularities [16,26]. Related expansions that do not satisfy the differential equation and hence need fitting in the interior of a domain, not just on the boundary, lead to least-squares methods for radial basis functions (RBFs) or other kernels [10,14,21,29]. RBF methods are an example of the broad category of meshfree methods.…”
Section: Introductionmentioning
confidence: 99%
“…Our plan is to set forth some of the simplest methods for solving rectangular eigenproblems and to illustrate them with a sequence of examples. The closest previous contributions we know of on this topic are by Manzhos and coauthors, who have developed what they call "rectangular collocation" methods for eigenvalue problems in quantum chemistry [21,22], and by the first two authors [17]. The emphasis in [17] is on spectral methods for ODEs, and the linear algebra is carried out by the method of Ito and Murota [19], involving the singular value decomposition (SVD) of a matrix with twice as many columns as there are basis functions.…”
Section: Introductionmentioning
confidence: 99%
“…With expansion functions that satisfy the differential equation but not the boundary conditions, one gets series methods [32] or the Method of Fundamental Solutions (MFS) [3,13] or lightning or log-lightning methods for PDE problems with corner singularities [16,26]. Related expansions that do not satisfy the differential equation and hence need fitting in the interior of a domain, not just on the boundary, lead to least-squares methods for radial basis functions (RBFs) or other kernels [10,14,21,29]. RBF methods are an example of the broad category of meshfree methods.…”
Section: Introductionmentioning
confidence: 99%
“…Our plan is to set forth some of the simplest methods for solving rectangular eigenproblems and illustrate them with a sequence of examples. The closest previous contributions we know of on this topic are by Manzhos and coauthors, who have developed what they call "rectangular collocation" methods for eigenvalue problems in quantum chemistry [21,22], and by the first two authors [17]. The emphasis in [17] is on spectral methods for ODEs, and the linear algebra is carried out by the method of Ito and Murota [19], involving the singular value decomposition (SVD) of a matrix with twice as many columns as there are basis functions.…”
Section: Introductionmentioning
confidence: 99%